Caught between vulgar and effete realists: Critical theory, classical realism and mythographies of power. (February 2017) - Luke, Timothy W
This study explores conceptual conflicts embedded in the thematic grounding of classical realism. To establish conditions of consistent normality in human political behaviour for realist analysis, the rhetoric of originary political wisdom usually ties its claims, as a research framework, to myth and enlightenment. Because Thucydides, Machiavelli or Hobbes articulated the premises of political realist analysis in the contexts of state formation, anarchic regional politics and perpetual war, these first figures of political authority seem to have set terms of geopolitical analysis that erase context, arrest temporality and homogenise space by pointing analysis back to classical events, thinkers and struggles in mythic terms. Critical theorists ask if such mythic styles of reasoning are a credible approach, even though many accept such modes of analysis. Consequently, this study explores how myth affects political realist studies to question how statecraft perpetuates itself on reason, myth and their contradictions.